The association between social factors and body length proportions in Polish schoolchildren from Lower Silesia - Kozieł, Sławomir; Gomula, Aleksandra; Nowak-Szczepańska, Natalia (Anthropological Review, 2016)
Many studies worldwide have shown that social factors are significantly associated with growth in childhood. However, very few researchers studied influence of social factors on body length proportions. The aim of the present study was the assessment how urbanization level, sibship size and parental education may affect body length proportions in schoolchildren. 325 boys and 335 girls aged 7-18 years were measured in schools in Wrocław, two small towns and villages around these towns. Height, sitting height, leg length , and lower leg length were measured in all children, then relative lengths (in relation to height) were calculated: leg, femur, lower leg, estimated leg and lower leg length to leg length ratio. Height was standardized on age using LMS parameters for CDC 2002 year cohort. Other indices were standardized on age by using residuals variance derived from linear regressions. Four-way analysis of variance was used for height and each index, where independent variables were four social factors. Except for father’s education in boys, no other social factor was significant associated with height. Urbanization level significantly differed almost all indices, whereas father’s education level was significantly associated with relative leg length in girls and estimated leg length in both sexes. Our study has shown that the segments of lower limb seems to be more sensitive than height to the effect of social factors. In Lower Silesia, the level of urbanization is still related to differences in environmental conditions, enough to significantly affect growth of children, especially within the segments of lower limbs.